The evolution of logic - Hart, W. D. (Wilbur Dyre) 1943- (Cambridge Cambridge University Press, 2010)
"Examines the relations between logic and philosophy over the last 15 years. Logic underwent a major renaissance beginning in the nineteenth century. Cantor almost tamed the infinite, and Frege aimed to undercut Kant by reducing mathematics to logic. These achievements were threatened by the paradoxes, like Russell's. This ferment generated excellent philosophy (and mathematics) by excellent philosophers (and mathematicians) up to World War II. This book provides a selective, critical history of the collaboration between logic and philosophy during this period. After World War II, mathematical logic became a recognized subdiscipline in mathematics departments, and consequently but unfortunately philosophers have lost touch with its monuments. This book aims to make four of them (consistency and independence of the continuum hypothesis, Post's problem, and Morley's theorem) more accessible to philosophers, making available the tools necessary for modern scholars of philosophy to renew a productive dialogue between logic and philosophy"--Provided by publisher.
1. Cantor's paradise -- 2. Die urwahrheiten -- 3. Expeditions: which sets exist? -- 4. The universe and everything -- 5. Truth eludes proof -- 6. Accommodating Cantor -- 7. Or not -- 8. The critique of pure reason -- 9. The ways of the world -- 10. The zoology of reality.
Includes bibliographical references (pages 281-290) and index.
Keywords: Logic -- History